Bioimaging: Near‐Infrared Fluorescent Nanomaterials for Bioimaging and Sensing (Advanced Optical Materials 2/2017). Issue 2 (January 2017) - Reineck, Philipp; Gibson, Brant C.
Abstract : Near‐infrared light can penetrate biological tissue much deeper than visible light. Therefore, near‐infrared fluorescent nanomaterials, reviewed in article number 1600446 by P. Reineck and B. C. Gibson, are critical for the development of light‐based biomedical imaging techniques to create new windows into the living body. The image by Marco Capelli shows light exciting nanoparticles in a blood vessel. The particles emit near‐infrared light that can be detected for example to create an image of the vasculature for real‐time fluorescence‐image‐guided surgery.